Solar Irrigation for Female Farmers and Farmer Groups in Northern Ghana - Obeng Adomaa, Faustina (2025)
This infographic presents strategic partnership between small and medium scale agricultural enterprises, supported with technical assistance from AICCRA through the International Water Management Institute (IWMI) leading to the development and deployment of Solar Irrigation solution for women farmers and farmer groups in Northern Ghana. This bundled strengthened female vegetable farmers’ resilience while promoting gender and social inclusion.